2021
DOI: 10.1177/15266028211007468
|View full text |Cite
|
Sign up to set email alerts
|

Iliac Conduits for Endovascular Treatment of Aortic Pathologies: A Systematic Review and Meta-analysis

Abstract: Purpose: The treatment of thoracoabdominal aortic aneurysm has largely shifted to endovascular techniques. However, severe iliofemoral arterial disease often presents a challenge during these interventions. As a result, iliac conduits have been introduced to facilitate aortic endovascular therapy. The goal of the current study was to gauge utilization and to analyze iliac artery conduit outcomes to facilitate endovascular therapy to treat aortic pathologies. Materials and Methods: A meta-analysis of 14 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…In particular, there is a strong recommendation for smoking cessation at least 2 weeks before aneurysm repair, 2 yet over 30% of patients in our cohort were current smokers at the time of intervention. Our data also demonstrated that patients with 30-day MACE were more likely to require open vascular access and iliac conduits, suggesting a greater degree of systemic atherosclerosis 33 . Therefore, there are important opportunities to improve care for patients by understanding their surgical risk and medically optimizing them before intervention.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In particular, there is a strong recommendation for smoking cessation at least 2 weeks before aneurysm repair, 2 yet over 30% of patients in our cohort were current smokers at the time of intervention. Our data also demonstrated that patients with 30-day MACE were more likely to require open vascular access and iliac conduits, suggesting a greater degree of systemic atherosclerosis 33 . Therefore, there are important opportunities to improve care for patients by understanding their surgical risk and medically optimizing them before intervention.…”
Section: Discussionmentioning
confidence: 58%
“…Our data also demonstrated that patients with 30-day MACE were more likely to require open vascular access and iliac conduits, suggesting a greater degree of systemic atherosclerosis. 33 Therefore, there are important opportunities to improve care for patients by understanding their surgical risk and medically optimizing them before intervention. In addition, we demonstrate the contribution of anatomic complexity to adverse outcomes because of distal AAA extent and prior EVAR, which is corroborated by previous literature.…”
Section: Explanation Of Findingsmentioning
confidence: 99%
“…Hay diversas publicaciones que describen una mayor estancia hospitalaria, pérdida hemática y mortalidad a 30 días en pacientes que requieren conductos iliofemorales (9,17,18). Nuestra experiencia es muy distinta, incluso aunque nuestra serie es sobre F/BEVAR; sin embargo, es cierto que nosotros realizamos los conductos permanentes siempre en un procedimiento previo.…”
Section: Discussionunclassified
“…Hostile iliac access is an obstacle to perform endovascular aneurysm repair (EVAR), and it reportedly precludes EVAR in 6-15.4% of patients with abdominal aortic aneurysms (AAA) (Arko et al 2004). These occlusive iliac accesses are manageable in most cases by endovascular revascularization alone or combining surgical procedures such as creating iliac conduit for delivery of the endograft (Uchiyamada et al 2013;Vallabhaneni et al 2012;Takeuchi et al 2019;Giannopoulos et al 2021). However, in cases where the occlusion of the iliac artery extends to the common femoral artery (CFA), a concomitant surgical intervention such as endarterectomy of the CFA is also necessary.…”
Section: Introductionmentioning
confidence: 99%